A Day in the Life of the U.S. Capitol Building: January 6, 2021 in Seven Scenes. Issue 2 (3rd July 2021) - Kulper, Amy Catania; Liu, Lucy Siyao; Bohne, Matthew
Abstract : On January 6, 2021, Donald Trump summoned a mob of angry supporters from across the country to Washington DC, where they were to join the president at a "Save America" rally. The premise for the rally was Trump's oft-repeated and patently false claim that the 2020 presidential election had been "stolen" from him. In a speech given at the Ellipse, Trump incited the crowd, warning "If you don't fight like hell, you're not going to have a country anymore." 1 Provoked by his incendiary rhetoric, the enraged crowd marched to the US Capitol Building, demanding that Vice President Mike Pence and Congress reject Joe Biden's victory. Their intention was to disrupt the Electoral College vote count by Congress that would ratify the election results, and they did so by breaching, vandalizing, and looting both the grounds and the US Capitol Building. Five people died as a result of the storming of the US Capitol and more than 140 people were injured, with the insurrectionists causing upwards of thirty million dollars in damages. In the days following the insurrection, the shock and awe at the televisual and social media spectacle of the riot registered globally. The building stories that follow will consider these events from the vantage point of the architecture that housed them, utilizing architectural representational conventions to consider the roles that the built environment played in the insurrection.